1988
DOI: 10.1159/000234512
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Clinical Course of <i>Treponema pallidum </i>Infection in Guinea Pigs

Abstract: The clinical course of infection with Treponema pallidum (Nichols) in inbred strain 2 guinea pigs was shown to be affected by age, sex and site of inoculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Indeed, the clinical and pathological consequences of TP infection in natural and experimental syphilis relate to a variety of factors native to both the host and the parasite. Age and sex unquestionably affect the clinical course of infection (for references, see 3), and temperature is one of the most influencial of the environmental factors affecting the course of treponemal infection (4). Moreover, accumulating evidence has suggested that natural susceptibility or resistance to TP infection is genetically determined.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the clinical and pathological consequences of TP infection in natural and experimental syphilis relate to a variety of factors native to both the host and the parasite. Age and sex unquestionably affect the clinical course of infection (for references, see 3), and temperature is one of the most influencial of the environmental factors affecting the course of treponemal infection (4). Moreover, accumulating evidence has suggested that natural susceptibility or resistance to TP infection is genetically determined.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of a readily available inbred strain of rabbits has been a stumbling block in our understanding of the effector mechanisms operative in the process of immunity in syphilis. We have shown that Treponema pallidum infection in an inbred strain of guinea pigs, although milder than in rabbits, mimics critical aspects of the early stage of venereal syphilis in humans when carried out under optimal conditions (15). A number of basic parameters such as median infective dose, clinical course of infection, and humoral and cellular responses have been explored in different strains of guinea pigs (for a review, see reference 13).…”
mentioning
confidence: 99%